2018
DOI: 10.3389/fmicb.2018.00442
|View full text |Cite
|
Sign up to set email alerts
|

Skin Microbiomes of California Terrestrial Salamanders Are Influenced by Habitat More Than Host Phylogeny

Abstract: A multitude of microorganisms live on and within plant and animal hosts, yet the ecology and evolution of these microbial communities remains poorly understood in many taxa. This study examined the extent to which environmental factors and host taxonomic identity explain microbiome variation within two salamander genera, Ensatina and Batrachoseps, in the family Plethodontidae. In particular, we assessed whether microbiome differentiation paralleled host genetic distance at three levels of taxonomy: genus and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 65 publications
3
44
2
Order By: Relevance
“…Although we did not observe any signs of disease in the Batrachoseps attenuatus sampled in Eucalyptus dominated habitats (other than lower body condition indices), it is possible that an increase in Chlamydiaceae in the skin of salamanders results from microbial dysbiosis (Prado-Irwin et al, 2017). Other skin microbiota studies on terrestrial salamanders in the San Francisco Bay Area have identified Chlamydiaceae taxa on the skin microbial communities; however, the relative abundances of this taxa are usually rare as we observed in salamanders inhabiting Quercus habitat (Bird et al, 2018). While we cannot effectively link the increase in Chlamydiaceae to infectious disease in our salamanders, it is important that future studies on terrestrial salamanders evaluate whether this bacterial group poses a threat to the health of amphibians in disturbed habitats.…”
Section: Differences In Community Heterogeneity and Relative Abundanccontrasting
confidence: 59%
See 1 more Smart Citation
“…Although we did not observe any signs of disease in the Batrachoseps attenuatus sampled in Eucalyptus dominated habitats (other than lower body condition indices), it is possible that an increase in Chlamydiaceae in the skin of salamanders results from microbial dysbiosis (Prado-Irwin et al, 2017). Other skin microbiota studies on terrestrial salamanders in the San Francisco Bay Area have identified Chlamydiaceae taxa on the skin microbial communities; however, the relative abundances of this taxa are usually rare as we observed in salamanders inhabiting Quercus habitat (Bird et al, 2018). While we cannot effectively link the increase in Chlamydiaceae to infectious disease in our salamanders, it is important that future studies on terrestrial salamanders evaluate whether this bacterial group poses a threat to the health of amphibians in disturbed habitats.…”
Section: Differences In Community Heterogeneity and Relative Abundanccontrasting
confidence: 59%
“…However, the association between host microbiotas and the habitat microbial pool vary among studies. Among wild populations in relatively natural habitats, some studies have found that microbiomes vary significantly with habitat type (Bird et al, 2018;Bletz et al, 2017) whereas others have found that microbiomes are relatively conserved and coevolve with hosts (Prado-Irwin et al, 2017). Thus, whether changes in the local microbial community structure also affect host microbial symbionts remains an open question.…”
Section: Introductionmentioning
confidence: 99%
“…) and the skin microbiota of congeneric salamanders (Bird et al . ; Muletz Wolz et al . ) suggest that a shared environment can drive community similarity more strongly than host phylogenetic proximity.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in an individual bacterial isolate's interactions with the environment and other microbes are also known to alter bacterial metabolite production (Daskin et al, 2014;Wolz et al, 2017;Medina et al, 2017a;Bird et al, 2018). Thus, another consideration is whether Bd is present and when is it most active, as changes in microbial community composition have been linked with the onset of Bd infection (Pullen et al, 2010;Longo et al, 2015;Clare et al, 2016;Varela et al, 2018).…”
Section: Spatial and Temporal Variation Within Genera And Speciesmentioning
confidence: 99%